I want the solution of this question
Attachments:
![](https://hi-static.z-dn.net/files/d60/13d6f5264aa3609351e80d02b95d6fac.jpg)
Answers
Answered by
1
x+y = a+b, and ax-by = a^2 -b^2
Now multiply the first equation with b, you will get
bx + by = ab + b^2.
Now add equation 2 and 3,
ax + bx = a^2 + ab
Solving this you will get x=a and y=b
Now multiply the first equation with b, you will get
bx + by = ab + b^2.
Now add equation 2 and 3,
ax + bx = a^2 + ab
Solving this you will get x=a and y=b
Vaibhav786:
i am confused how u add the equation 2 and 3 define it clearly plzzz
Similar questions
Social Sciences,
9 months ago
Geography,
9 months ago
Math,
1 year ago
Science,
1 year ago
India Languages,
1 year ago